Research the load capacity of microcircuits - Katerina S. Yarantseva; Gennady P. Shopin; Mikhail N. Piganov; Vladimir S. Andrusenko (Физика волновых процессов и радиотехнические системы, 2020)
The device for the definition of the integrated circuits load-driving capability is offered. Device for determining the output capability of microcircuits refers to the field of microminiaturization and the technology of radio electronic equipment and can be used to control the parameters of microcircuits during their production. The device contains a rectangular pulse generator, an integrated circuit that is being tested, a repeater, load, a switch, an AND gate, a comparator, a pulse counter and a voltage reference, a vibrator, a reversible pulse counter, a decoder, and an indicator. Technical result when implementing the disclosed solution is high accuracy and reliability of determining load capacity of microcircuits. The proposed device allows increasing accuracy and reliability of defining circuits load-driving capacity. It also allows testing of TTL, Schottky-TTL, and MOSFET circuits. There are two switchable operating modes for testing fan-out for logical high and low levels. It is easy to replace a circuit that is being tested and load.